2014
DOI: 10.1186/1751-0759-8-22
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic responses in adolescent chronic fatigue syndrome: contributions from expectancies as well as gravity

Abstract: BackgroundOrthostatic intolerance is common in chronic fatigue syndrome (CFS), and several studies have documented an abnormal sympathetic predominance in the autonomic cardiovascular response to gravitational stimuli. The aim of this study was to explore whether the expectancies towards standing are contributors to autonomic responses in addition to the gravitational stimulus itself.MethodsA total of 30 CFS patients (12–18 years of age) and 39 healthy controls underwent 20° head-up tilt test and a motor image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In contrast, Wyller et al. () did not find an abnormal response to the standard version of this task, whereas when asked to imagine standing upright, adolescents with CFS showed a significantly stronger increase in sympathetic predominance compared to healthy controls. This indicates that abnormal responses to the head‐up tilt task in adolescents with CFS are not purely the result of the gravitational challenge.…”
Section: Introductionmentioning
confidence: 82%
“…In contrast, Wyller et al. () did not find an abnormal response to the standard version of this task, whereas when asked to imagine standing upright, adolescents with CFS showed a significantly stronger increase in sympathetic predominance compared to healthy controls. This indicates that abnormal responses to the head‐up tilt task in adolescents with CFS are not purely the result of the gravitational challenge.…”
Section: Introductionmentioning
confidence: 82%
“…The abovementioned factors result in an increase in the body’s tension in the anti-gravity mode [ 1 – 4 , 6 , 29 , 32 , 35 , 39 , 49 , 51 , 58 ], which actually leads to the development of fatigue syndrome. Several studies have demonstrated an association between chronic fatigue syndrome and orthostatic intolerance, predominantly postural orthostatic tachycardia syndrome [ 7 , 59 , 60 ].…”
Section: Changes In the Cardiovascular System During Postnatal Ontogenesis As An Anthropogenic Basis For The Physiology And Pathology Of mentioning
confidence: 99%
“…This may make exercise harder physically, perpetuating avoidance of it. Through experience, physical activity may become associated with increased fatigue by classical conditioning (10)(11)(12). Furthermore, in theory, expectations may influence the experience of fatigue, creating a vicious cycle whereby the expectation of fatigue being induced by exercise makes it more likely that an individual attends to signs of fatigue in response to exercise.…”
mentioning
confidence: 99%